Peran Rohani Islam dalam Pembinaan Akademik Siswa pada Mata Pelajaran Pendidikan Agama Islam di SMA Negeri 1 Lembah Melintang Pasaman Barat - Mardiatun Nisa Nst; Mustafa Mustafa (YASIN, 2026)
Islamic Spirituality activities (Rohis) play an important role as a means of academic and religious development for students in Islamic Religious Education subjects at public schools. This study aims to analyze the role of Rohis in students’ academic development and to identify the supporting and inhibiting factors in the implementation of Rohis activities at SMA Negeri 1 Lembah Melintang, West Pasaman. This study used a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving the principal, vice principal for student affairs, Islamic Religious Education teachers, Rohis supervisors, Rohis administrators, and students participating in Rohis activities. Data were analyzed through the stages of data reduction, data display, and conclusion drawing, with triangulation techniques used to ensure data validity. The results showed that Rohis plays an important role in students’ academic development through three main aspects, namely the development of Islamic insight, the development of religious interests and talents, and religious skills training. Rohis activities help students deepen Islamic Religious Education material, improve their abilities in da’wah, public speaking, Qur’anic recitation, and worship practice, and have a positive impact on learning outcomes and the formation of students’ religious character. Supporting factors for the implementation of Rohis include school support, the availability of facilities and infrastructure, and students’ need for religious development, whereas inhibiting factors include limited time, uneven student participation, and limited activity funding. The conclusion of this study affirms that Rohis plays a strategic role in supporting academic development and strengthening students’ religious character at school. These findings provide practical implications for schools in optimizing religious extracurricular activities as part of strengthening Islamic Religious Education learning.